Can Brodifacoum Save Endangered Species? Recent Experiences from the West Indies. (1st April 2018) - Daltry, Jenny; Bell, Elizabeth
Commensal rats – in particular the black, ship or roof rat (Rattus rattus), Polynesian rat (R. exulans) and brown or Norway rat (R. norvegicus) – stand accused of a long list of offences against humankind, from destroying crops and food stores to gnawing power cables and spreading diseases. Their impacts on wildlife have been even more disastrous. Wherever people have gone, these adaptable rats have followed and multiplied. Island ecosystems have especially suffered as the omnivorous rodents have flourished with few, if any, natural predators to curb them. Rats have colonised all but a handful of the 7, 000 islands in the West Indies, devastating native biodiversity (Figure 1). Since 1500, these Caribbean islands – a mere 0.15% of the Earth's land area – have accounted for 10% of the world's bird extinctions, 35% of mammal extinctions and over 65% of reptile extinctions. Over two-thirds of extinctions on islands are attributed to invasive alien mammals, especially rats. Conservationists are now fighting back using rodenticides designed for controlling rats in cities and farms. Since the early 1990s, over 40 rat eradication operations have been accomplished on Caribbean islands to save wildlife. This article describes two of the most ambitious operations to date, some of the lessons learned, and their effects on native wildlife. The projects to eradicate black rats from Dog Island in 2012 and Redonda in 2017 were logistically challenging but went according to plan using predominantly ground-based methods. While more labour intensive than aerial baiting, the use of bait stations allows for much greater control over the quantity and distribution of bait, further reducing the risk to non-target animals. Based on this experience – combined with more than two dozen operations in this region – brodifacoum can be used safely and effectively to eradicate rats from Caribbean islands, with almost zero risk to native wildlife as long as the right bait and methods are used. With bait placed at intervals of not more than 40 metres, our primary bait Klerat? appeared fully successful in eradicating the rats within 4 weeks. Contrary to concerns by some operator, the bittering agent Bitrex did not deter the black rats from consuming the bait but may have helped prevent other animals from eating it. At the time of writing, a further six islands in Anguilla and Antigua are scheduled for the removal of invasive alien rodents using the same bait, including islands home to endangered Lesser Antillean iguanas, Sombrero ground lizards and lignum vitae trees (Guaiacum officinale). A growing number of such animals and plants owe their recovery to rat eradications, and islands that have been cleared of rats can in turn become attractions to nature-loving tourists and enjoyed by local people. There are thousands of islands that still have invasive alien rats, and whose native biodiversity is dwindling. In this race to prevent more island species becoming extinct, brodifacoum is proving to be one of the greatest tools that conservationists have.